Utility of the serum alanine aminotransferase to high density lipoprotein cholesterol ratio in evaluating nonalcoholic fatty liver disease and liver fibrosis - Yanyan Xuan; Dingting Wu; Yuhong Jin; Xuxia Yu; Jingbo Yu; Yinwei Zhang (Scientific Reports)
Abstract The association of the serum alanine aminotransferase to high-density lipoprotein cholesterol ratio(ALT/HDL-C) with NAFLD remains unclear. This study aimed to examine the association of the ALT/HDL-C ratio with the prevalence of NAFLD and liver fibrosis in the U.S. general population. 4764 participants from the 2017–2018 National Health and Nutrition Examination Survey were included in our cross-sectional study. The association of ALT/HDL-C with NAFLD was examined using a general additive model. Furthermore, we conducted subgroup analyses to evaluate the relationship between liver fibrosis, NAFLD risk, and the ALT/HDL-C ratio. Of the 4764 participants, 1513 (31.76%) were diagnosed with NAFLD. All three logistic regression models showed positive associations between NAFLD risk and ALT/HDL-C. Furthermore, in stratified analyses by body mass index (BMI), gender, and age, ALT/HDL-C was positively associated with NAFLD. Hepatic steatosis and fibrosis severity were strongly linked with the ALT/HDL-C. The ALT/HDL-C and the incidence of NAFLD exhibited a nonlinear distribution that was particularly noticeable in women with an inverted U distribution with an inflection point of 0.528. NAFLD was more accurately predicted by ALT/HDL-C than by ALT or HDL-C alone, according to receiver operating characteristic (ROC) analysis. A higher ALT/HDL-C ratio in the U.S. population is independently associated with a significantly higher risk of NAFLD and liver fibrosis. The ALT/HDL-C ratio is a useful noninvasive diagnostic tool to quickly and accurately identify those at high risk of developing NAFLD and liver fibrosis.